Factors affecting the apathy towards access and awareness of information in traditional newspapers among Vietnamese university students - Huyen, Nguyen Thị (Edelweiss Applied Science and Technology, 2025)
The present research examines the contributions to the apathy of Vietnamese university students toward seeking and consuming information from traditional newspapers. Using a sample of 200 university students in Hanoi, a multivariate linear regression analysis was conducted to assess five main factors: digital preference, perceived relevance, engagement with content, lifestyle and mobility, and environmental concerns. The results indicate that all five factors have a significant influence on students’ disinterest in traditional newspapers. The results suggest that the tendency of students to prefer digital access, along with the perception that newspapers are neither relevant nor engaging, has contributed to apathy toward traditional newspapers. In addition, studens’ mobile lifestyles and environmental concerns have likely driven them away from print media. The results of this study suggest that traditional newspapers need to adapt to the market by enhancing their digital footprint, improving relevance of content, and addressing sustainability issues. These research findings will be helpful for media practitioners as they attempt to engage younger audiences within rapidly digitizing Vietnam.